Gas Heating and Formation of Single Linear Discharge Channel on Repetitive Branched Streamer Corona. Issue 2 (January 2015) - Matsumoto, Takao; Kijima, Koji; Shimoju, Toshiharu; Inada, Yoichi; Izawa, Yasuji; Nishijima, Kiyoto
SUMMARY Under a nonuniform field in an atmospheric short gap, a branched pulse streamer corona changes to a single filamentary discharge (SFD) for a split second just before sparkover occurs. This SFD is a pretransitional phenomenon of sparkover. Therefore, it is very important to study SFD for an understanding of the sparkover mechanism. In this work, the SFD was recreated well by applying a highly repetitive impulse voltage to a needle‐plane gap in synthetic air with dilute CO2. The characteristics of the SFD, including the channel temperature, the propagation of the streamer head, and the formation process, were investigated by means of an intensified charge coupled‐device (ICCD) camera and a spectroscopic measurement system. It was found that the transition to SFD progresses with localized gas heating along the discharge channel. Furthermore, it was revealed that the SFD is a nonbranched positive streamer.